Influence of the APOE genotypes in some atherosclerotic risk factors - Martins, M. Carmo (2009)
The aim of this work was to study the distribution of apolipoprotein E (APOE) genotypes and their association with some atherosclerotic risk factors, all of them modifiable: total, HDL and LDL cholesterol, triglycerides, systolic and diastolic blood pressure, BMI, waist circumference and smoking. The sample population was constituted of 672 healthy subjects recruited in the Lisbon area. Lipids were quantified by usual automatic enzymatic methods and the APOE genotypes performed in accordance with Hixson and Vernier. Blood pressure measurement and hypertension classification followed international specifications. The frequency distribution of APOE alleles was: epsilon2 = 6.4%, epsilon3 = 83.6% and epsilon4 = 10.0% and the more prevalent genotypes were epsilon2/epsilon3, epsilon3/epsilon3 and epsilon3/epsilon4 respectively 11.0%, 70.1% and 16.1%. We could only observe associations among the most prevalent genotypes and lipids, always statistically significant, specially when the epsilon4 allele was present which was even proved by an higher prevalence of epsilon4 in dyslipidemic subjects with the only exception of those with low HDL-c values. A stronger intervention in the epsilon4 carriers is so recommended through appropriate intervention measures on the connected modifiable risk factors.